Water in Protic Ionic Liquid Electrolytes: From Solvent Separated Ion Pairs to Water Clusters. Issue 16 (12th July 2021) - Gehrke, Sascha; Ray, Promit; Stettner, Timo; Balducci, Andrea; Kirchner, Barbara
Abstract: The large electrochemical and cycling stability of "water‐in‐salt" systems have rendered promising prospective electrolytes for batteries. The impact of addition of water on the properties of ionic liquids has already been addressed in several publications. In this contribution, we focus on the changes in the state of water. Therefore, we investigated the protic ionic liquid N ‐butyl‐pyrrolidinium bis(trifluoromethanesulfonyl)imide with varying water content at different temperatures with the aid of molecular dynamics simulations. It is revealed that at very low concentrations, the water is well dispersed and best characterized as shared solvent molecules. At higher concentrations, the water forms larger aggregates and is increasingly approaching a bulk‐like state. While the librational and rotational dynamics of the water molecules become faster with increasing concentration, the translational dynamics are found to become slower. Further, all dynamics are found to be faster if the temperature increases. The trends of these findings are well in line with the experimental measured conductivities. Abstract : From single molecules to bulk liquid : The state of water in a protic ionic liquid at different concentration is investigated by the aid of molecular dynamics simulations. At a low concentration, the water shows the behavior of free molecules. With increasing concentration, the formation of clusters can be observed. Finally, at concentrations near the phase separation the behavior approaches that of the bulk liquid.